Acidentes por abelhas (apis mellifera) no estado do Rio Grande do Norte, Brasil - Santos, Cícera Emanuelly Evangelista (Universidade Federal Rural do Semi-Árido, 2017)
Bees (Apis mellifera) are insects of the order Hymenoptera of relevant human interest, as they contribute socially as economic value and help to maintain the flora of the planet. However, accidents due to these insects are common in Brazil, occurring quite frequently in humans and domestic animals, and represent a serious public health problem due to its casuistry and possibility of causing serious reactions, with a rapid evolution to death. The objective of this research was to describe the epidemiological aspects of bees' accidents in the State of Rio Grande do Norte from 2007 to 2015. Data were collected from the Health Information System database - DATASUS, of the Ministry of Health, through the Notification of Injury Information System (SINAN) and Mortality Information System (SIM). There were 2.526 accidents by bees in the State and 17 deaths in the study period, with lethality of 0.7%. Over the years, the incidence was upward and 120 municipalities (71.9%) from all regions registered cases. The time of year with the highest occurrence of accidents comprised between May and October (60.3%). Males were more affected (64.5%) and in the age group 20-39 (48.2%), corresponding to young adults. Considering the information presented here, bee accidents represent a public health problem, requiring more research and effective prevention strategies aimed at reducing accidents and avoiding deaths.
Monografia
Keywords: Animais peçonhentos; Epidemiologia; Saúde pública; Venomous animals; Epidemiology; Public health; CIENCIAS AGRARIAS::MEDICINA VETERINARIA